The determinants of post-IPO return in Malaysia stock market / Nur Hazirah Hamdan - Hamdan, Nur Hazirah (Faculty of Business and Management, 2011)
This research is study on the financial income variables towards post-IPO return. The scope of the study has focuses on the return of IPO as a result shows from the company’s financial performance proxies by liquidity, profitability, leverage and asset utilization. The objective of the study is to determine the significant correlation between company’s financial income variables towards post-IPO return. The independent variables of this study are Quick Ratio (QR), Net Profit Margin (NPM), Debt Equity Ratio (DER) and Asset turnover (ATO) as a financial ratio represented the company’s performance. While for dependent variables, it is return for post-IPO and been measure in 5 days preliminary from the first day it’s been issued. The data period cover from year 2005-2010 and retrieved from historical price sources provided by data stream and performance of company’s financial income gathered the data from prospectuses published in Thomson One Banker. The multiple linear regression model is use to investigate the relationship between financial income variables with post-IPO return by using Econometric Views (E-Views 6.0). From the findings, only (DER) variables show significance correlation and able to effect post-IPO return and its express positively relationship. While, for others three variables, QR, NPM, and ATO shows no significant impact to the returns. The result shows consistently in 5 days return and its concludes that, from investors’ point of view, financial performance of companies are not strongly reflect in decision making on investment.